Analisis Kepuasan Konsumen Point Kupi Kabupaten Aceh Barat - Aulia, Muhammad Reza; Harinal, Harinal; Ananda, Fadilah Nazmi; Dalimunthe, Wahyulita; FZ, Malika Rahmah; Murnisyati, Murnisyati (Universitas Katolik Santo Thomas Medan, 2023)
Demonstrating customer satisfaction is important for marketers because it is often considered a fairly important determinant of repeat purchases. This study aims to analyze consumer satisfaction with services and products at Point Kopi. A survey method was used with a structured questionnaire to collect data from respondents. Statistical analysis will be conducted to evaluate consumer perceptions of service quality, products, and other factors that may affect satisfaction levels. Based on the results of the Customer Satisfaction Index (CSI) analysis, it produces a value of 84.55% which indicates that overall consumers are very satisfied with Point Kupi. This shows that Point Kupi's performance is in accordance with consumer expectations.